2015
DOI: 10.1136/gutjnl-2015-309458
|View full text |Cite
|
Sign up to set email alerts
|

TGR5 is essential for bile acid-dependent cholangiocyte proliferation in vivo and in vitro

Abstract: TGR5 is an important mediator of BA-induced cholangiocyte proliferation in vivo and in vitro. Furthermore, TGR5 protects cholangiocytes from death receptor-mediated apoptosis. These mechanisms may protect cholangiocytes from BA toxicity under cholestatic conditions, however, they may trigger proliferation and apoptosis resistance in malignantly transformed cholangiocytes, thus promoting CCA progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
155
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 84 publications
9
155
0
4
Order By: Relevance
“…The results showed that these markers were significantly decreased, suggesting that murine cholangiocyte proliferation was inhibited. In addition, expression of the transmembrane-bound G protein-coupled receptor (Tgr5) that is activated by bile acids (especially tLCA and tDCA) (Keitel and Haussinger, 2013;Duboc et al, 2014;Reich et al, 2016) and localized in cholangiocytes and modulates cholangiocyte proliferation and bile flow, was lower (Fig. 3B).…”
Section: Instability Of the Chimeric Humanized Liver Mouse Modelmentioning
confidence: 99%
“…The results showed that these markers were significantly decreased, suggesting that murine cholangiocyte proliferation was inhibited. In addition, expression of the transmembrane-bound G protein-coupled receptor (Tgr5) that is activated by bile acids (especially tLCA and tDCA) (Keitel and Haussinger, 2013;Duboc et al, 2014;Reich et al, 2016) and localized in cholangiocytes and modulates cholangiocyte proliferation and bile flow, was lower (Fig. 3B).…”
Section: Instability Of the Chimeric Humanized Liver Mouse Modelmentioning
confidence: 99%
“…Bile acids have been shown to alter platelet activation [35] and aggregation [26] and are elevated in BDL mice and in mice fed with a cholic acid diet [36]. To test, if bile acids account for the observed activation defects of BDL platelets, a chow enriched with 0.5% cholic acid, a physiological bile acid in the mouse, was given ad libitum for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…L'activation de TGR5 par les acides biliaires secondaires stimule la prolifération et inhibe l'apoptose des cholangiocytes [5]. Au niveau des macrophages, TGR5 limite la production de cytokines pro-inflammatoires [6].…”
unclassified